(untitled) (Itinera, 2025)
This review discusses Johann Michel’s Lire les images. Herméneutique de l’art (PUF, 2025), emphasizing its original contribution to philosophy of art seen through the lens of an approach grounded in philosophical hermeneutics. Michel articulates a genuinely hermeneutic approach to the “imaginal,” understood as a lived, embodied, and historically sedimented event of meaning. Drawing primarily on Gadamer and Ricoeur, he builds the book as a dialogical space in which art history, semiotics, iconology and visual studies, phenomenology, psychoanalysis, pragmatism, and cultural anthropology intersect without being reduced to a unique paradigm. The review highlights Michel’s capacity to reveal how artworks emerge from, and return to, the lifeworld, preserving traces of experience and configuring new pathways of interpretation. By connecting the imaginal with the ontological dimension of historicity, Michel shows how the artwork continues to walk through time, interpellating us at the same time as embodied subjects, provoked and engaged by the work of art at the aesthetic level of affects and feelings, and as interpretive subjects who put in place a methodical distanciation necessary to explain them more in order to understand them better. The review argues that this book represents a significant advancement in the philosophy of the image and a compelling expansion of hermeneutics into the visual domain.